Actual consciousness - Ted Honderich (Oxford: OUP, 2014)
What is it for you to be conscious? There is no agreement whatever in philosophy or science: it has remained a hard problem, a mystery. Is this partly or mainly owed to the existing theories not even having the same subject, not answering the same question? In Actual Consciousness, Ted Honderich sets out to supersede dualisms, objective physicalisms, abstract functionalism, externalisms, and other positions in the debate. He argues that the theory of Actualism, right or wrong, is unprecedented, in nine ways.
Keywords: Mind; Consciousness; Cognitive Science; Psychology